The Effect of Digital Marketing, E-payment, and Service Quality on Sales Revenue of Culinary MSMEs in Tenda Santai Sejenak - Yuni Irmawan; Idhina Ghustina; Bambang Sutejo (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
In the midst of the current era of digitalization, technological advances have provided various conveniences for entrepreneurs. Technological development is a development that cannot be avoided in everyday life. The culinary MSMEs of Tenda Santai Sejak have a fairly high level of income in 2020 and above. the purpose of the study was to determine the effect of Digital Marketing, E-Payment and Quality Service on the sales revenue of culinary MSMEs in Tenda santai sejak. The type of research method used in this research is quantitative method, The population of this study were customers of MSMEs Tenda Santai Sejak with a total of 712 people. The sample of this study involved 90 respondents. The data used is primary data or data obtained directly from respondents, the data collection method used by researchers is to distribute questionnaires to customers of the Tenda Santai Sejenak UMKM directly by sampling using the sovlin technique. Based on partial hypothesis testing, it is concluded that there is an effect of Digital-Marketing and E-payment on Sales Revenue at Tenda Santai Sejenak and there is no effect of Quality Service on Sales Revenue at Tenda Santai Sejenak.Based on the results of this study, it can be concluded that the absence of digital marketing in an MSME business in the era of globalization like now greatly affects its sales revenue, not only with Digital Marketing but E-payment also has an effect on increasing MSME sales, because nowadays consumers choose not to be complicated in transactions.